Automatic and Obstacle Avoidance in Metal Detector Robot - Mohd Zin, Zatie Adiba; Ali, Fuead; Ab Kadir, Diyana (Journal of Computing Technologies and Creative Content, 2016)
This project aims to develop a mobile robot that can sense metals ahead of its path. Usage of this robot is reserved only in the house and on the flat surfaces. The metal detector robot is controlled by a microcontroller; Arduino Uno R3. Ultrasonic sensor detects the presence of objects or obstacles and the robot will avoid the obstacles. The metal detector uses inductive proximity sensor to detect metals. Also, it will be able to alarm user when metal is detected.